An overlooked view at weber s DAN solvatochromic probes: photosensitization and photostability - Sandoval-Altamirano, C (ELSEVIER SCIENCE SA, 2026)
DAN derivatives, and particularly LAURDAN, are widely used fluorescent probes to explore membrane structure, dynamics, and phase transitions. Their pronounced sensitivity to polarity and hydration has established them as important tools for fluorescence microscopy and biophysical studies. However, despite the extensive physicochemical understanding and usage, fundamental knowledge about their photostability and degradation pathways remains limited. Photobleaching and probe inactivation are well-known drawbacks that compromise fluorescence measurements, yet no systematic description of these processes exists in the literature for DAN-based probes. In this work, we studied DAN derivatives having different acyl group flexibility in different solvents. Our results show that fluorescence behavior strongly depends on the solvent, with rigidized derivatives showing enhanced emission in polar protic media. All compounds exhibited enhanced photosensitization in apolar solvents, whereas inside lipid bilayers the activity was modest. Photodecomposition studies with LAURDAN revealed solvent-dependent stability, with extensive bleaching in acetonitrile but only modest degradation in ethanol and toluene. HPLC analysis showed the formation of multiple products, some retaining chromophoric features. These results provide the first systematic description of DAN probe degradation, offering important knowledge for their reliable application and interpretation of their behavior in membrane research and fluorescence imaging.